Adoro Te devote – a synthesis of St. Thomas Aquinas's eucharistic theology - Gotia, Andrei (Verbum – Analecta Neolatina, 2004)
In this article, the author analyzes closely the most famous Eucharistic hymn written by St. Aquinas, Adoro Te devote, in the light of passages from the Summa Theologiae which treat the Holy Eucharist. In looking at Fra Angelico's La Crocefissione, which contains one of the renowned portraits of St. Thomas, the author finds similarities with the hymn.